The Strategic Management Process for Innovation Activities of HAYA Water, Oman - Al Alawi, Adil Said (Advances in Social Sciences Research Journal, 2021)
The main objective of this research is to investigate and explore the entrepreneurship and innovation in the Sultanate of Oman, taking the example of selected organisation that operates its business in the country, Haya Water, and explore the different innovation strategies which are essential for business growth and sustainability. The research study is based on the information gathered from previously published journals for the literature review and information through direct interview with employees in the company for the innovation strategy that is implemented in the company. The strategic management process for innovation activities that are driven by certain internal and external forces of Haya Water Oman will be explored as well in this research study. This will discuss the forces that initiate the innovation and entrepreneurship in this organisation, with the key factors for successful creation and implementation of innovation process within the organisation. It will also cover some discussions on the limitation that delay the progress and development of innovation with recommended mitigation actions to overcome these challenges.